Enterovirus 71 Induces INF2 Cleavage via Activated Caspase-2 in Infected RD Cells - Wang, Bei; Zhang, Chongyang; Yu, Congci; Zhu, Yue; Tang, Qing; Huang, He; Zhao, Zhendong (Frontiers in Microbiology, 2021)
Enterovirus 71 (EV71) is the major causative pathogen of hand, foot, and mouth disease. The lack of understanding of the virus’s pathogenesis hinders the development of anti-virus drugs and the control of EV71 infection. Our previous studies have demonstrated that both mitochondria and endoplasmic reticulum (ER) were altered significantly in EV71 infected cells, but the mechanism is still unclear. In this study, we investigated the effects of EV71 infection on the expression of INF2, a key regulator factor in ER-Mitochondria communication and mitochondrial fission. We found that INF2 was cleaved in EV71 infected RD cells. The INF2 cleavage occurred at Aspartic 1,051 of INF2 and is mediated by activated caspases, predominantly by activated caspase-2. The subcellular localization of INF2 and caspase-2 was significantly altered in infected cells. We speculate that caspase-2-mediated INF2 cleavage is involved in forming viral replication organelles (ROs) and is a positive feedback regulatory mechanism of mitochondrial disorders caused by EV71 infection.